Computer Digital Technology-Based Educational Platform for Protection and Activation Design of Ming Furniture. (17th December 2021) - Peng, Zhe; Du, Yichen
Abstract : Chinese Ming-style furniture is the first of the three major furnitures in the world, which has high artistic value and complete structural system. The protection of Ming-style furniture and making its design show vitality that has always been a research topic in China and even in the world. Based on 3D virtual simulation technology, this paper uses 3D scanning reverse data acquisition technology and intelligent operation of computer engine to realize big data simulation and develops the design software of Ming furniture. By means of computer information technology, we interpret and present the structural thinking and design concept of Ming furniture and transform it into design program software. This has formed a system-wide educational software operation platform for knowledge reserve, thinking training, design and application, and achievement transformation. By applying the mechanism strategy of production and teaching to the talent training plan of colleges and universities, the underlying logic of talent training, technical management, and production management that can open up the innovative industry of Ming furniture is also constructed. After experimenting with the platform software, students are able to understand the relationship between the structure and form of Ming furniture and can design new styles that fit the logic of Ming furniture shapes as they prefer.